2023
DOI: 10.3390/antib12010004
|View full text |Cite
|
Sign up to set email alerts
|

TLR7 and IgM: Dangerous Partners in Autoimmunity

Abstract: The B cell antigen receptor (BCR)-repertoire is capable of recognizing a nearly unlimited number of antigens. Inevitably, the random nature of antibody gene segment rearrangement, needed in order to provide mature B cells, will generate autoreactive specificities. Once tolerance mechanisms fail to block the activation and differentiation of autoreactive B cells, harmful autoantibodies may get secreted establishing autoimmune diseases. Besides the hallmark of autoimmunity, namely IgG autoantibodies, IgM autoant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 87 publications
0
4
0
Order By: Relevance
“…It has also been demonstrated that gut microbiota induces a homeostatic humoral response, not only restricted to IgG, but also IgA and IgM. Therefore, we determined all three classes ( 53 ) against the most abundant bacteria in the gut of TLR7Tg mice. Although we found an increased adaptive IgG2c and IgA response in TLR7Tg mice against B. acidifaciens , the IgM response was unexpectedly higher.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been demonstrated that gut microbiota induces a homeostatic humoral response, not only restricted to IgG, but also IgA and IgM. Therefore, we determined all three classes ( 53 ) against the most abundant bacteria in the gut of TLR7Tg mice. Although we found an increased adaptive IgG2c and IgA response in TLR7Tg mice against B. acidifaciens , the IgM response was unexpectedly higher.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, given heat inactivation, washing, and use of healthy control serum in the assay, this also demonstrated that IgM alone was sufficient to stimulate pathologic complement activity in some cases of CM-HUS. Together these results suggest a role for both "natural, polyreactive" and "autoreactive" IgM in the disease 51 .…”
Section: Pre-sensitization Of Piga or Dko Cells With Cm-hus Sera And ...mentioning
confidence: 72%
“…Our bi-variate Mendelian randomization analysis intimates that Type 1 Diabetes, Multiple Sclerosis, and Rheumatoid Arthritis exert deleterious effects on anemia, with multivariable MR substantiating the detrimental interrelation among Type 1 Diabetes, Multiple Sclerosis, and anemia. These adverse associations may be mediated through mechanisms pertinent to immune responses 49 , chronic in ammation, and drug interactions. In Type 1 Diabetes, the autoimmune apparatus erroneously targets pancreatic β-cells, a dysregulation similarly manifested in certain anemic conditions 50 .…”
Section: Discussionmentioning
confidence: 99%